Penyuluhan Pola Hidup Bersih dan Sehat (PHBS) dalam Rangka Pencegahan Gagal Ginjal Kronik Pada Anak di Sekolah Dasar Tanjung Mas Semarang - Ainnur Rahmanti; Syurrahmi Syurrahmi; Ni Kadek Krisna (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Chronic kidney failure is a serious health problem that not only attacks adults, but can also develop since childhood. One of the main risk factors is unhealthy living habits, including lack of personal hygiene, consumption of unhealthy food, and minimal physical activity. In order to increase awareness regarding the importance of a clean and healthy lifestyle among children, health education efforts are needed from an early age, especially in schools as an environment where children spend a lot of time. Many children do not understand the relationship between personal hygiene, diet and kidney health. Based on the results of interviews with teachers and school health staff, there are several unhealthy behaviors among students, such as rarely washing their hands, excessive consumption of sweet drinks, and low daily physical activity. In addition, only a few students understand the importance of maintaining hydration and adequate water intake for kidney health. This outreach activity will be carried out in several stages, including counseling about the importance of a clean and healthy lifestyle, demonstrations teaching correct hand washing and distribution of leaflets about information on a clean and healthy lifestyle.